The Use of Marketing Slogans in Municipal Marketing - selected aspects - Czopek, Miłosz; Kijowska, Olena (Linguistic creativity in marketing, 2022)
Municipal marketing plays a crucial role in the positioning of local governments on the investment, tourist and cultural markets. In the study, the authors present the determinants of municipal marketing, indicate the factors which have significantly contributed to its development and list the recipients of internal and external activities related to municipal marketing. The study also presents the results of research on the importance and effectiveness of city and town advertising slogans in public perception, the best communication channels used for promotion purposes and their characteristic features. The article also shows the results of the analysis of three slogans advertising towns located in the Dolnośląskie [ Lower Silesia ] Voivodeship.